Automation of boron chromatographic purification for δ11B analysis of coral aragonite. (23rd April 2020) - de la Vega, Elwyn; Foster, Gavin L.; Martínez‐Botí, Miguel Angel; Anagnostou, Eleni; Field, M. Paul; Kim, M. Hwan; Watson, Paul; Wilson, Paul A.
Abstract : Rationale: To detect the small changes in past pH, the boron isotope ratio of coral carbonates, expressed as the δ 11 B value, needs to be both precise and accurate (2sd <<1‰). Boron measurements by Multi‐Collector Inductively Coupled Plasma Mass Spectrometry (MC‐ICPMS) require the boron to be carefully purified before analysis, which is time consuming, and requires specialist training. Here, we use the prepFAST‐MC method that enables the automatic extraction of B (up to 25 ng load) from a CaCO3 matrix. Methods: Samples were purified using the prepFAST‐MC automated system with a 25‐μL column of Amberlite IRA743 resin. Boron isotope measurements were performed by MC‐ICPMS. The effects of matrix load, speed of sample loading onto the column, and blank contamination were tested to evaluate the effects on the purification process. The optimised protocol was tested on various standards and samples of aragonite corals. Results: The blank contribution for the approach is 60 pg and is negligible given our sample size (<0.2% sample size). Efficiency of matrix removal is demonstrated with the addition of up to 1.6 mg of dissolved low‐B calcium carbonate to NIST SRM 951 with no impact on the accuracy of δ 11 B values. The Japanese Geological Survey Porites reference material JCp‐1, boric acid standard NIST SRM 951, and seawater, all processed on the prepFAST‐MC system, give δ 11 B values within error of literature values (δ 11 BJCp‐1 = 24.31 ± 0.20‰ (2sd, n = 20); δ 11 BNIST 951 = −0.02 ± 0.15‰ (2sd, n = 13) and δ 11 BSeawater = 39.50 ± 0.06‰ (2sd, n = 2)). Results obtained from the coral Siderastrea siderea purified with the prepFAST‐MC system show an average offset from the manual ion‐exchange protocols of Δδ 11 B = 0.01 ± 0.28‰ (2sd, n = 12). Conclusions: Our study demonstrates the capacity of the prepFAST‐MC method to generate accurate and reproducible δ 11 B values for a range of materials, without fractionation, with efficient matrix removal and with negligible blank contribution.